MnS/MnO heterostructures with dual ion defects for high-performance aqueous magnesium ion capacitors - Minghui Liu; Mudi Li; Siwen Zhang; Yaxi Ding; Ying Sun; Jiazhuo Li; Haixi Gu; Bosi Yin; Hui Li; Tianyi Ma (Journal of Magnesium and Alloys)
The advancement of aqueous magnesium ion energy storage devices encounters limitations due to the substantial hydration radius of magnesium ions (Mg2+) and their strong electrostatic interaction with the primary material. Consequently, this study successfully developed a MnS/MnO heterostructure through a straightforward hydrothermal and annealing method, marking its initial application in aqueous magnesium ion capacitors (AMICs). The fabricated MnS/MnO heterostructure, characterized by S defects, also generates Mn defects via in-situ initiation of early electrochemical processes. This unique dual ion defects MnS/MnO heterostructure (DID-MnS/MnO) enables the transformation of MnS and MnO, initially not highly active electrochemically for Mg2+, into cathode materials exhibiting high electrochemical activity and superior performance. Moreover, DID-MnS/MnO enhances conductivity, improves the kinetics of surface redox reactions, and increases the diffusion rate of Mg2+. Furthermore, this study introduces a dual energy storage mechanism for DID-MnS/MnO, which, in conjunction with dual ion defects, offers additional active sites for Mg2+ insertion/deinsertion in the host material, mitigating volume expansion and structural degradation during repeated charge-discharge cycles, thereby significantly enhancing cycling reversibility. As anticipated, using a three-electrode system, the developed DID-MnS/MnO demonstrated a discharge specific capacity of 237.9 mAh/g at a current density of 0.1 A/g. Remarkably, the constructed AMIC maintained a capacity retention rate of 94.3% after 10000 cycles at a current density of 1.0 A/g, with a specific capacitance of 165.7 F/g. Hence, DID-MnS/MnO offers insightful perspectives for designing alternative clean energy sources and is expected to contribute significantly to the advancement of the clean energy sector.